Музеефикация как форма культурной трансляции - Дружинина, Е.С. (Культура народов Причерноморья, 2014)
В статье анализируется процесс осознания человеком темпорального расслоения культуры и его поиска устойчивых форм сохранения и трансляции артефактов, ценностей и смыслов, одной из которых выступает музеефикация. Культурология имеет дело с постоянно развивающимся сознанием, которое существует во временном пространстве прошлого и настоящего. Музей стал формой визуальной коммуникации, поскольку обеспечивал наглядную и реальную коммуникацию с культурой прошлого посредством сохранившихся артефактов. У статті аналізується процес усвідомлення людиною темпорального розшарування культури і його пошуку стійких форм збереження і трансляції артефактів, цінностей і смислів, однією з яких виступає музеєфікація. Культурологія має справу з свідомістю, яке існує в часовому просторі минулого і сьогодення. Музей став формою візуальної комунікації, оскільки забезпечував наочну і реальну комунікацію з культурою минулого за допомогою збережених артефактів. The article analyzes the process of man's awareness of the temporal separation of culture and his search for stable forms of preservation and transmission of artefacts, values and meanings. Museumification serves one of these forms. Man functions under two systems that reflect the temporal view of culture. It is a system of traditions as cultural expressions of the past and the system of reality as the experience of the present culture. Any system generates and displays its properties in the process of interaction with the environment. Culture doesn’t exist and can’t exist without communication. The communication promotes and provides coverage of cultural meanings from one generation to another. Technical progress promotes transformation of forms of cultural transmission. At the present stage of development of culture the opportunity to participate in various social processes remotely (to learn, to visit museums, to "walk in guests" on skype, etc.) changes both temporal and spatial characteristics of the human reality. Museum becomes a form of visual communication because it provides a visual and real communication with the culture of the past through the preserved artifacts. Since then, the very form of collecting artifacts gave impetus to museumification in culture. The transformation of the artifact into the exhibit is always the recognition of cultural, historical, social or educational value.